PENGARUH KEPERCAYAAN DIRI DAN MOTIVASI BERPRESTASI TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 8 SURAKARTA - -, Nurani -; -, Sunarto -; -, Dewi Kusuma Wardani - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The objectives of this research are to find out: (1) The influence of self-confidence and achievement motivation to students learning achievement on Economic Subjects of students in grade XI of Social Science Programof SMA Negeri 8 Surakarta in the academic year 2017/2018. (2) The influence of self-confidence to students learning achievement on Economic Subjectsof students in grade XI of Social Science Programof SMA Negeri 8 Surakarta in the academic year 2017/2018. (3) The influence of achievement motivation to students learning achievement on Economic Subjects of students in grade XI of Social Science Programof SMA Negeri 8 Surakarta in the academic year 2017/2018. This research was descriptive quantitative research with hypothesis testing. Located in SMA Negeri 8 Surakarta. The population wasthe students of grade XI Social Science which are 106 students. The samples were 51 students taken by using proportional random sampling technique. The data of the research was collected through questionnaire. The technique of analyzing the data is multiple regression analysis.The result of this research are: (1) There is a positive and significant influence between self-confidence to student achievement obtained the result of tcount confidence of 2.334, while the value of ttable of 2.011. (2) There is a positive and significant influence between achievement motivation toward student achievement of obtained the value of tcount variable achievement motivation that is equal to 2,273 while value ttable 2.011. (3) There is a positive and significant influence between self-confidence and achievement motivation jointly to student achievement in grade XI of Social Science Programof SMA Negeri 8 Surakarta shown with Fcount value of 9,135, while Ftable value equal to 3,191. The amount of influence of confidence variable and achievement motivation toward achievement result of learners obtained from calculation of R square equal to 27,6%, while the rest (100%-27,6% = 72,4%) influenced by other causes such as environmental factor learning in school, family environmental factors, interest in learning, and learning media.